Financial Literacy as a Moderator of the Effects of Fintech Payment, Income, and Hedonic Lifestyle on Impulse Buying among Generation Z - Priskila Panjaitan; Anwar Azazi; Ana Fitriana; M. Ridwan Ristyawan; Anggraini Syahputri (Al-Qalam Institue, 2026)
This study aims to examine the influence of fintech payment usage, income, and hedonic lifestyle on impulse buying behavior among Generation Z, as well as to analyze the moderating role of financial literacy in these relationships. A quantitative approach was employed using a cross-sectional survey design. The sample consisted of 280 respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using moderated regression analysis with SmartPLS version 4.1.1.6. The results indicate that fintech payment usage, income, and hedonic lifestyle have positive and significant effects on impulse buying behavior. Financial literacy significantly weakens the relationship between hedonic lifestyle and impulse buying. However, it does not significantly moderate the effects of fintech payment usage and income on impulse buying. These findings imply that improving financial literacy can serve as a strategic mechanism to reduce the negative impact of a hedonic lifestyle on impulsive purchasing decisions. The study contributes to the literature on consumer behavior by highlighting the protective role of financial literacy in the digital financial ecosystem and provides practical insights for policymakers and financial educators in designing interventions to promote responsible consumption among young consumers.